2020
DOI: 10.1080/13880209.2020.1739719
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of Camellia nitidissima aqueous ethanol extract against CCl4-induced acute liver injury in SD rats related to Nrf2 and NF-κB signalling

Abstract: Context: Camellia nitidissima Chi (Theaceae) is an evergreen shrub, the leaves of which are used in many medicinal applications. Objective: To characterize the chemical composition of a 10% aqueous ethanol extract of C. nitidissima leaves (CNE), and to explore the protective effect of the extract against acute liver injury (ALI) in rats. Materials and methods: Male Sprague-Dawley rats were divided into six groups (n ¼ 10): control and negative (0.5% CMC-Na, 5 mL/kg/d), thiopronin (20 mg/kg/d) and CNE (40, 80 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Recently, herbal medicines have attracted increasing attention in the treatment of alcoholic liver injury, due to the wide availabilities, multitarget actions, and low side effects [ 14 16 ]. Chinese herbal medicines of saponins from the leaves of Panax notoginseng , Camellia nitidissima, and phenol have been used to improve the alcohol-induced liver injury [ 6 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, herbal medicines have attracted increasing attention in the treatment of alcoholic liver injury, due to the wide availabilities, multitarget actions, and low side effects [ 14 16 ]. Chinese herbal medicines of saponins from the leaves of Panax notoginseng , Camellia nitidissima, and phenol have been used to improve the alcohol-induced liver injury [ 6 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The result verified that C. nitidissima Chi leaf extraction exhibited a good effect on the inhibition of pancreatic lipase. When compared with C. nitidissima Chi flower extract reported in previous studies, which was more effective than the C. nitidissima Chi leaf extract (Zhang, Feng, et al, 2020; Zhang, Wu, et al., 2020).…”
Section: Resultsmentioning
confidence: 72%
“…Identification of individual compounds in C. nitidissima Chi leaf extraction was performed by UHPLC–MS/MS, the chromatogram obtained in the UHPLC was shown in Figure 2. Eight compounds were identified in the C. nitidissima Chi leaf extraction which could be seen in Table 1, using UHPLC–MS/MS based on their molecular masses, fragmentation patterns, and literature references (Duc et al, 1993; Karthivashan et al., 2013; Li et al., 2016; Makita et al., 2016; March et al., 2006; Qiu et al., 2015; Taskin et al., 2020; Wang et al., 2016; Zhang, Feng, et al, 2020; Zhang, Wu, et al., 2020). Among these individuals, multiflorin B(5,7‐dihydroxy‐2‐(4‐hydroxyphenyl)‐4‐oxo‐4H‐1‐benzopyran‐3‐yl 6‐deoxy‐4‐O‐β‐D‐glucopyranosyl‐α‐L‐mannopyranoside), kaempferol‐3‐O‐rutinoside, vicenin‐2(5,7‐dihydroxy‐2‐(4‐hydroxyphenyl)‐6,8‐bis[(2S,3R,4R,5S,6R)‐3,4,5‐trihydroxy‐6‐(hydroxymethyl) oxan‐2‐yl] chromen‐4‐one), apigenin‐6‐C‐pentosyl‐8‐C‐hexosyl, vitexin(5,7‐dihydroxy‐2‐(4‐hydroxyphenyl)‐8‐[(2S,3R,4R,5S,6R)‐3,4,5‐trihydroxy‐6‐(hydroxymethyl) oxan‐2‐yl] chromen‐4‐one), kaempferol, vinaginsenoside R9(2‐[4,5‐dihydroxy‐2‐[[12‐hydroxy‐17‐[5‐hydroxy‐6‐methyl‐2‐[3,4,5‐trihydroxy‐6‐(hydroxymethyl)oxan‐2‐yl]oxyhept‐6‐en‐2‐yl]‐4,4,8,10,14‐pentamethyl‐2,3,5,6,7,9,11,12,13,15,16,17‐dodecahydro‐1H‐cyclopenta[a]phenanthren‐3‐yl]oxy]‐6‐(hydroxymethyl)oxan‐3‐yl]oxy‐6‐(hydroxymethyl)oxane‐3,4,5‐triol), and 20‐glc‐ginsenoside Rf((2S,3R,4S,5S,6R)‐2‐[(2R,3R,4S,5S,6R)‐2‐[[(6R,10R,12S,14R,17S)‐3,12‐dihydroxy‐4,4,10,14,15‐pentamethyl‐17‐[(2S)‐6‐methyl‐2‐[(2S,3R,4S,5S,6R)‐3,4,5‐trihydroxy‐6‐(hydroxymethyl)oxan‐2‐yl]oxyhept‐5‐en‐2‐yl]‐1,2,3,5,6,7,8,9,11,12,13,15,16,17‐tetradecahydrocyclopenta[a]phenanthren‐6‐yl]oxy]‐4,5‐dihydroxy‐6‐(hydroxymethyl)oxan‐3‐yl]oxy‐6‐(hydroxymethyl)oxane‐3,4,5‐triol) or its isomer appeared to be the main components in C. nitidissima Chi leaf extracts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the results of recent studies have shown that the pathogenesis of ALI can be blocked by the inhibition of inflammatory responses (Starkey Lewis et al, 2020). In summary, anti-inflammatory therapies are effective in treating ALI (Chen et al, 2020;Zhang et al, 2020). It is, however, necessary to clarify the underlying mechanism of effective targets for ALI caused by sepsis in view of the fact that there is no current effective treatment for ALI (Bae et al, 2018).…”
Section: Introductionmentioning
confidence: 99%